Determinant of The Corporate Social Responsibility Disclosure: Evidence of Indonesian Manufacturing Companies - Ikhsan, Arfan; Nurlaila, Nurlaila; Suprasto, Herkulanus Bambang; Batubara, Febi Yanti (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 16 No 1 (2021), 2021)
Following the necessity to provide transparent information on social activities, corporate social responsibility (CSR) disclosure is important for companies in Indonesia. This study aims to examine and analyze the effect of information ofCEO Power (CEOP), Board Capital (BCAPDUM), Media Disclosure (PMED), and Profitability (ROA) on CSR. This research usedmanufacturing companies listed on the IDX in 2016 as the subject. Using thepurposive sampling method, 26 companies were selected as the research sample. Research findings showed thatCEOP, PMED, and ROA haveastatistical effect on CSR disclosure, whereas BCAPDUM has no effect on CSR disclosure. Therefore, CEOP, PMED, and ROA have a positive and significant effect on CSR disclosure. Keywords :   CEO Power, Board Capital, Media Disclosure, Profitability, CSR